Juridical Analysis of the Tradition of Consuming Tritis (Case Study of the Muslim Community in Karo from 2011 to 2022) - Sitepu, Fahri Roja; Tanjung, Dhiauddin; Syahputra, Akmaluddin (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2024)
The Law on Consuming Tritis from the Perspective of the Fatwa of the Indonesian Ulema Council (MUI) of North Sumatra Province No. 5 of 2011 Concerning the Law on Tritis and Law No. 33 of 2014 of the Republic of Indonesia Regarding Halal Product Assurance (Case Study of the Muslim Karo Community from 2011-2022) This journal explores the traditions of the Muslim Karo community in consuming tritis in relation to the implementation of the MUI North Sumatra Province Fatwa No. 5 of 2011, which discusses the legal status of consuming tritis. Tritis, a traditional food derived from undigested cow food processed with certain spices, holds significant cultural meaning for the Muslim Karo community. This study aims to explain the practice of consuming tritis in the Karo region and how these practices align with the religious guidelines provided by the MUI fatwa. Using an empirical juridical research approach and case study methodology, this research includes observations, interviews, and document studies. Through qualitative data analysis and deductive reasoning, this study examines the consumption habits of the Muslim Karo community and evaluates them based on the fatwa's provisions. The findings show that the tradition of consuming tritis is deeply embedded in Karo culture, influenced by long-held beliefs about the health benefits of tritis and the ease of obtaining its ingredients. However, the legal status of consuming tritis, as outlined by the MUI Fatwa No. 5 of 2011, states that the practice is haram because it derives from animal materials prohibited under Islamic law. The implementation of this fatwa has been inadequate due to a lack of religious knowledge, insufficient fatwa socialization, and deeply rooted cultural factors.